The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jcdd9030083
|View full text |Cite
|
Sign up to set email alerts
|

Open Coronary Endarterectomy of Left Anterior Descending Artery—Case Report and Review of Literature

Abstract: Coronary endarterectomy (CE) emerged as a necessity to achieve complete surgical myocardial revascularization in patients with diffusely diseased coronary arteries and it also serves as aid to coronary bypass grafting (CABG). The safety and postoperative prognosis of this procedure are still matters of debate. There are no clear preoperative indications, a standard technique has not yet been established as gold standard and the postoperative management differs depending on each institution. CE of the left ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The next step in CABG was using bilateral mammary arteries (BIMA). Similar angiographic patency rates were reported between left and right internal mammary arteries [4,5], and multiple studies reported higher survival rates when using BIMA [6][7][8]. Multiple studies report a higher rate (2.5%) of deep SSI a so-called "never event" when BIMA is used [9,10].…”
Section: Introductionsupporting
confidence: 52%
“…The next step in CABG was using bilateral mammary arteries (BIMA). Similar angiographic patency rates were reported between left and right internal mammary arteries [4,5], and multiple studies reported higher survival rates when using BIMA [6][7][8]. Multiple studies report a higher rate (2.5%) of deep SSI a so-called "never event" when BIMA is used [9,10].…”
Section: Introductionsupporting
confidence: 52%
“…The presence of an easily concealable scar reduces the psychological stress associated with operated heart disease. For this reason, there is a worldwide trend in performing more congenital procedures via thoracotomy, in children as well as in adults [ 13 , 21 , 22 ]. One difference between the two groups is that, in children, central cannulation is easier, due to the short distance between the chest wall and the great vessels.…”
Section: Discussionmentioning
confidence: 99%